An Gottes Wirken zur Erneuerung der Schöpfung teilhaben: Für Klimagerechtigkeit einstehen als Ausdruck ökologischer und sozialer Heiligung - Wenner, Rosemarie (Theologie für die Praxis, 2025)
June 21,2025, the World Council of Churches launched a Decade of Climate Justice Action. Building up on the Methodist tradition, theology and practice, I explore why climate justice action must become an integral part of Christian discipleship. I refer to the Wesleyan understanding of sanctifying grace and the invitation to serve as co-workers in God’s new creation, as well as to spiritual resources that lead to metanoia and renewal, highlighting an invitation to renew our understanding of Holy Communion, which unites us not only with Christ and one another, but also with creation.